Disclosure Quality, the Cost of Capital and Strategic Correlation - Cheung, Adrian; Hu, Wei (Centre for Research in Applied Economics, 2014)
We investigate the strategic role of correlation between disclosure error and payoff shock in affecting a firm’s cost of capital or share price. We show that the correlation affects the relationship between disclosure quality and the cost of capital or share price. The standard result where disclosure quality unambiguously lowers the firm’s cost of capital or share price can be observed only in the case where the correlation is zero. In the extreme case where the correlation is perfect, disclosure quality does not affect the cost of capital or share price. When compared to other non-perfect correlation cases, the extreme case where the correlation is perfect results in, on average, a higher share price. This implies that the firm can achieve a higher share price by influencing the correlation (i.e., making it nonzero) and suggests a new way as to how the effectiveness of a disclosure should be evaluated.